Contribution of students in the evaluation of master’s and doctoral programs in the field of nursing - Ferreira, José Erivelton de Souza Maciel; Oliveira, Lídia Rocha de; Cavalcante, Tahissa Frota (Investigación y Educación en Enfermería, 2023)
Modern nursing has gained more space and scientific recognition. As a result, health postgraduate programs, including postgraduate education in nursing, are being increasingly expanded and implemented in numerous universities, higher education institutions, public and private colleges and institutes in several countries of the world. At the same time, more Check forupdatesContribution of students in the evaluation of master’s and doctoral programs in the field of nursing nurses have sought qualification in the field of teaching, research and professional practice, thereby resorting to master’s and doctoral programs, specialization programs and MBA courses. Master’s and doctoral programs are the most sought after in the world nowadays. This demand has required from bodies responsible for education that these programs find new ways of qualifying the training of professionals who decide to ascend in the academic career. Therefore, having broken the banking model of education in higher education in most countries of the world, postgraduate students started to contribute directly to the qualification of these programs, even though their contribution still needs more recognition and seriousness in educational institutions.